Inoculation of Acinetobacter johnsonii GY08 enhances faba bean (Vicia faba L.) growth under different salt concentrations - Awlachew, Zewdu; Mengistie, Gebeyehu; Degefa, Atsede; Bogale, Melese; Birhanu, Moges; Molla, Desilal (Journal of Agricultural Sciences (Belgrade), 2024)
One important environmental component that impacts plant growth and development, from seed germination to maturity, is salinity. The objective of this study was to examine the effect of inoculating salt-tolerant rhizobacteria on the morphological and physiological characteristics of faba bean under different salt concentrations in pot experimental conditions. The experiment contains six treatments with three replications in a completely randomized design, and the data was analyzed using one-way analysis of variance. The results showed that seed germination decreased by 4.16% and 8.33% with 150mM and 300mM salinity, respectively. However, the application of Rhizobacterium GY08 significantly enhanced seed germination by 4.16% and 6.38% with 150mM and 300mM salinity, respectively, compared to the un-inoculated treatments with the same salt concentration. Plants inoculated with GY08 showed higher biomass, shoot, and root elongation than the un-inoculated plants under both non-saline and saline conditions. The findings indicated that GY08 facilitated growth and enabled faba bean seedlings to flourish under salinity stress conditions by accumulating more proline content in comparison to un-inoculated plants. Therefore, further studies on various varieties and field conditions are recommended.